A ZigBee Test Performance with DHT11 Temperature sensor - adi, Puput Dani Prasetyo (Internet of Things and Artificial Intelligence Journal, 2021)
This study aims to examine the ability and Performance or Quality of Services of the IEEE 802.15.4 or ZigBee Radio Frequency module on the sensor node ZigBee based. Furthermore, ZigBee's communication capabilities i.e., Tree, Star, and mesh networking were developed on the internet or Internet of Thing using RaspBerryPi 4 as the Internet Gateway. The sensors used e.g., Pulse sensor and temperature and Humidity Sensor. Moreover, the Spectrum Analyzer is used to measure the Radio Frequency Value (-dBm) per Channel (CH1 to CH12) on the Zigbee module (EDs and CN) communication at different distances,on the Mesh or Tree ZigBee Communication, ZR can be used, at Point to Point ZigBee, the role of ZR is neglected. Energy efficiency battery ZigBee sensor nodes need to be considered to obtain sensor nodes Long Life, moreover, RSSI (-dBm) is the key to the analysis of sensor node communication systems on different sensor node clustering, including Throughput, PacketLoss sensor data, and data analysis on Application Server.